mRNA-based vaccines for the prevention of coronavirus infection - S. M. Kharit; I. V. Fridman (Журнал инфектологии)
Since March 2020, the World Health Organization has declared a coronavirus infection pandemic. Almost immediately, the development of vaccines began, according to the recommendations published by WHO. Currently, 137 vaccines in the world are undergoing clinical trials and 194 are at the stage of preclinical studies. Candidate vaccines have been developed using a variety of technology platforms. This article presents data on the safety and efficacy of mRNA vaccines against a new coronavirus infection in children and adolescents. A high population effect of these vaccines was noted before the spread of Delta and Omicron variants and a slight decrease in effectiveness against new coronavirus variants. The results of the use of these drugs in patients at risk are also described: cancer patients and people with autoimmune and autoinflammatory diseases.The review analyzed literature data on the safety and efficacy of mRNA vaccines against coronavirus infection. Currently used mRNA vaccines against novel coronavirus infection are safe and effective even among patients at risk (cancer patients and individuals with autoimmune or autoinflammatory diseases).The results of studies and post-registration monitoring of mRNA vaccines emphasize their safety and efficacy profile, which confirms the possibility and need for mass use.